If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(lnx + 1) = 0 Reorder the terms: 2(1 + lnx) = 0 (1 * 2 + lnx * 2) = 0 (2 + 2lnx) = 0 Solving 2 + 2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2lnx = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2lnx = 0 + -2 2lnx = 0 + -2 Combine like terms: 0 + -2 = -2 2lnx = -2 Divide each side by '2nx'. l = -1n-1x-1 Simplifying l = -1n-1x-1
| 0.10x+0.05(2-x)=0.10(5) | | 0.10x+0.05(2-x)=0 | | k^2-20k+64=0 | | 27x^6-27x^5+45x^3/-9x^3 | | 16-5(3t-4)=88(-2t+11) | | -8y=-33 | | 8y=-33 | | 5/12k=1/15-3/14 | | 85x-16=0 | | 6x-1=2x+1 | | cos(3x)-sin(2x)=0 | | 22-x=5+6x+9 | | 0=x^2-10x+28 | | 13y=1/15-3/14 | | -9x^2+4x-16=0 | | 3n^3+9n^2-84n=0 | | 4.90=0.05x+1.90 | | 3x-6=25x+18 | | 4(w-2)=0.6 | | 88-40=13/4(h-5) | | (2x-6)+(x+7)= | | 25-n^2=0 | | 23x-5=0 | | 12x-4x^2-9=0 | | 12q^2-17q+5=0 | | 6(x+2)=2(x+10) | | 25b+11-6b^2=0 | | 8x/6=72/54 | | 0.1q-0.2(3q+4)=-0.3(5q+3) | | 3x^3-10x^2-23x-10=0 | | k^2-2k+1=0 | | 0.15(w+2)=0.3+0.2w |